Prevalence of electrocardiographic abnormalities in heart failure patients attending Gujarat Adani institute of medical science, Kutch, Gujarat, India: a retrospective study - Thacker, Vinit A.; Trivedi, Jayesh V. (International Journal of Advances in Medicine, 2016)
Background: The ECG is a non-invasive and comparatively simple bedside test to perform. It is mostly utilized cardiovascular diagnostic test, and it is performed by cardiologists and other physicians who are not cardiologists. The ECG is an essential test in the evaluation of patients with heart failure. The aim was to establish the prevalence of electrocardiogram (ECG) abnormalities with heart failure patients attending department of medicine, Gujarat Adani Institute of medical science, Bhuj, Kutch, Gujarat, India. Methods: It was a retrospective study carried out department of medicine, Gujarat Adani Institute of medical science, Bhuj, Kutch, Gujarat, India. Simple random sampling technique was applied for medical records of 400 patients diagnosed with heart failure. The demographic, clinical, chest X-ray and 12-lead resting electrocardiographic (ECG) data of the patients were examined. Heart failure was diagnosed, by the modified Framingham criteria for the diagnosis of heart failure. Analysis was done using SPSS version 15 (SPSS Inc. Chicago, IL, USA) level of confidence interval and p value was set at 95% and 5% respectively. Results: The ECGs were abnormal in 92 % of the patients, and normal in 8% of the patients. The main ECG abnormalities included: left ventricular hypertrophy (42.9%), left axis deviation (39.8%), left bundle branch block (19.4%), and left atrial enlargement (25.80%). Arrhythmias seen included: ventricular extrasystoles (11.8%), atrial fibrillation (9.1%), complete heart block (5.7), and ventricular tachycardia (3.9%). Conclusions: ECG abnormalities are very frequent with heart failure patients in Bhuj, Kutch, Gujarat, India. The ECG is very helpful not merely in the analysis and etiology of heart failure but also it assists in recognizing significant complications of heart failure that might manipulate the option of treatment.